Design and Implementation of personal cloud network Using Network Attached Storage(NAS) - abd alrahem , Amani (University of Thi-Qar Journal, 2025)
Middleware is a key enabler of advanced digital transformation, simplifying the process of creating and managing smart applications, although its development poses significant challenges. The adoption of cloud software solutions has seen a significant increase, driven by their scalability, cost-effectiveness, and ease of deployment. As companies adopt these solutions to meet their software needs, the importance of customization within these cloud solutions becomes very important but somewhat complex and expensive. Customization may allow applications to be designed according to the specific requirements of the organization, enhancing user experiences and overall efficiency, but it does not enhance the capabilities of devices and personal use. NAS systems include user management capabilities that allow administrators to create user accounts, set up groups, and grant permissions on a per-file or per-share basis. This ensures that sensitive data can be kept secure while still allowing essential access to authorized users. Hence, the need for dedicated storage that facilitates cloud software-as-a- service solutions and a comprehensive examination of the benefits and challenges of customization within the cloud comes into play. As is well known, real-time resource-intensive applications require low latency, large data rates, and high computing and storage resources. Mobile cloud computing systems cannot meet the requirements of these applications due to high communication latency. For this reason, newly acquired edge computing applications are in dire need of a new design or a fundamental redesign. In addition, edge computing does not use the legacy capabilities of cloud computing. However, despite the many benefits, customization also poses challenges that must be addressed. The problem that will be discussed in this research paper is to enable the capabilities of mobile devices through more flexible and convenient uses of cloud resources through privacy in the process of information storage. This paper presents the motivation for using private networksTo overcome the challenges of cloud computing and mobile edge systems, propose a private mobile edge cloud in which mobile and fixed devices such as sensors, robots, home appliances, and smartphones are interconnected via wireless local area networks, based on the related infrastructure, creating a cloud data center in a small area with network storage space for ease of use. Also provides a general background and reviews with previous papers. Finally, the research is guided by a systematic exploration of interconnected private network storage solutions.